Literature and Economics. Another Way to Read the Text - Kisieliūtė, Ingrida (Respectus Philologicus, 2015)
At the end of the 20th century, the study of literature was supplemented by such new methods as biopoetics, geopoetics, new historicism, etc. The New Economic Criticism, a new approach to the literary text, was found in the United States in the late 20th century. The present article discusses the main aspects of the aforementioned area of the study of literature and as well presents the possible approaches to literary texts from the economic perspective. The New Economic Criticism does not aim to become a method or tendency; thus, it gives the freedom for a researcher to choose the perspective on the relationship between the literature and economics. The above-mentioned kind of analysis may be found in the English-speaking countries; whereas, the Russian literature has still remained unconsidered; however, Russian scholars are attempting to look at their fiction through the eyes of an economist. In Lithuania, the kind of research has not been found yet. Therefore, the article suggests one of the possible economic approaches, i.e., the analysis of the financial practices of the protagonist of The Gambler by F. Dostoyevsky.